Perceptions of Students on the Use of ChatGPT as a Translation Tool - Vinola, Vinvin; Supriusman, Supriusman; Syarfi, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This study investigates students’ perceptions of using ChatGPT as a translation tool. This study aims to find out the students’ perceptions of the use, advantages, and disadvantages of ChatGPT as a translation tool. This study used purposive sampling to find the sample. The total sample for this study was students who use ChatGPT as a translation tool, including 89 out of 109 students. This study used the explanatory sequential mixed method. The data was collected through 21 items of closed-ended questions and five items of open-ended questions. The researchers used descriptive statistical analysis for quantitative data and thematic analysis to find qualitative data. The findings showed that students’ overall perception of ChatGPT as a translation tool was high, with a mean score of 3.42. The construct on the use of ChatGPT as a translation tool was a moderate score (3.38), indicating that students use ChatGPT selectively to translate words, paragraphs, academic texts, and written assignments. The advantages of ChatGPT were rated high (3.56), indicating that students recognized its benefits in reducing proofreading and editing, saving time, language improvement, efficiency, and flexibility. However, the disadvantages were rated moderate (3.19), with concerns about dependency and translation quality. The study concludes that students positively perceived ChatGPT and recognized its limitations. Students use ChatGPT as a translation tool for only a few uses, and ChatGPT is a valuable tool for translation. However, students do not directly feel the disadvantages of ChatGPT because they use ChatGPT selectively.